EXPLORERS OF THE HIGHEST PLACES ON EARTH - Mavrikis, Peter (North Mankato, Minnesota : Capstone Press, 2021)
The amount of oxygen available at the highest place on Earth is just under 7 percent. Explorers risk their lives and test their lungs traveling to these great heights atop mountains. Who are these adventurers and why do they do it?
t t t Reinhold Messner.
Juvenile audience
Keywords: Explorers -- Biography -- Juvenile literature; Mountaineer -- Biography -- Juvenile literature; Mountaineering expeditions -- Everest, Mount (China and Nepal) -- Juvenile literature; Biographies; Juvenile works; Juvenile literature